(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The ancient Greeks were the “inventors” of more elements of civilization than any other people of the world. These elements of civilization can be viewed among historical writings especially associated with Herodotus and Thucydides, and the evolution of Democracy having foundational seeds in Athens. The Greeks view of the world was predominantly secular and rationalistic. It exalted the spirit of free inquiry and preferred knowledge to faith. With only a limited cultural inheritance of the past upon which to build, the Greeks produced intellectual and artistic monuments that had served ever since as standards of achievement. So in some ways the single most legacy of the ancient Greece is the civilization in India and ancient era is particularly influenced by the Greeks, especially in Art, language, culture and mostly covers the all aspects of Human life. This article is an attempt to explore cultural and religious evolution of India as an outcome of Indo Greek interaction. It further attempts to answer that why and how the India was influenced by the Greeks, Subsequently the Indian art particularly Gandhara appeared as the world’s famous Art of India.